GAMBARAN FUNGSI HATI PASIEN DIABETES MELITUS TIPE II DI SALAH SATU RUMAH SAKIT SWASTA DI KABUPATEN DEMAK PERIODE OKTOBER-DESEMBER 2020 - Pangestuningsih, Megi; Rukminingsih, Fef (Jurnal Riset Kefarmasian Indonesia, 2022)
Type II DM patients use Oral Antidiabetic Agent (OAA) continuously for a long time. OAA metabolism occurs in the liver. The use of OAA continuously in the long term can cause liver function disorders. The purpose of this study was to describe the liver function of type II DM patients who were treated with OAA in a private hospital in Demak District. This study is an observational descriptive study using retrospective data obtained from medical record documents of outpatients with type II DM for the period October – December 2020. Sampling using purposive sampling technique. The inclusion criteria were outpatients with type II DM, JKN participants who received OAA therapy for at least one year, aged 36 – 65 years old, have AST and ALT laboratory examinations. Patients who received combination therapy with insulin, had a history of impaired liver function were excluded. The results showed that from 62 patients there were 39 female patients (62.9%), the most patients aged 56-65 years were 32 patients (51.61%). The longest duration of use of OAA was 1 year, namely 29 patients (46.77%). The most widely used OAA was a combination of biguanides and sulfonylureas in 36 patients (58.07%). A total of 51 patients (82.25%) did not experience liver function damage and as many as 11 patients (17.75%) showed mild liver function damage with the duration of using OHO for more than 1 year and using OHO combination.